STRATEGI PEMERINTAH DESA DALAM MENJAGA KESTABILAN EKONOMI MASYARAKAT DESA DI MASA PANDEMI (Studi kasus di Desa Wolaang Kec. Langowan Timur Kab. Minahasa - TICOALU, SHANIA; RURU, JOORIE; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2021)
In this increasingly developing era, a nation is required to be able to design sustainable developmentstrategies in advancing its nation. This development can be in the form of physical development or otherresources, community empowerment as one of the methods or methods that can be used in the grandframework of national development. The purpose of this study was to determine Community Empowermentthrough the Immanuel Farmer Group Program in Raringis Village, West Langowan District, MinahasaRegency. The theory used in this study is the theory of Community Empowerment from Sumodiningrat(2007) which contains three stages of empowerment, namely the stage of awareness and behavior formation,the stage of transformation of work abilities, and the stage of increasing intellectual abilities. This studyuses descriptive qualitative research, namely to obtain more complete, more in-depth, credible andmeaningful data by conducting interviews with 8 informants and also by collecting documents related tocommunity empowerment so that the objectives of the research will be achieved. The results of this studydescribe community empowerment through the Immanuel farmer group program in Raringis Village, WestLangowan District, Minahasa Regency, it has been going quite well in terms of the application of the threeindicators of the empowerment stage.Keywords : Empowerment, Program, Farmer Group